The guilt trip [large type] - Jones, Sandie (Thorndike Press large print core series., 2022)
"Rachel and Jack. Paige and Noah. And Will. Five friends who've known one another for years. Then along came Ali, Will's new fiancée. The three couples travel to Portugal for Ali and Will's destination wedding. The weekend away at the gorgeous cliff-top villa is a chance to relax and get to know Ali an little better. She seems perfectly nice--and Will seems happy after years of bad choices. But when Rachel discovers a shocking secret about Ali, everything changes. As the wedding weekend unfolds, the secrets each of them holds begin to spill, and friendships and marriages threaten to unravel. In Sandie Jones's explosive new suspense novel, jumping to conclusions can become the difference between life and death"--